UBVH: Unified Bounding Volume and Scene Geometry Representation for Ray Tracing - Káčerik, M.; Bittner, J. (Computer graphics forum, 2025)
Bounding volume hierarchies (BVHs) are currently the most common data structure used to accelerate ray tracing. The existing BVH methods distinguish between the bounding volume representation associated with the interior BVH nodes and the scene geometry representation associated with leaf nodes. We propose a new method that unifies the representation of bounding volumes and triangular scene geometry. Our unified representation builds on skewed oriented bounding boxes (SOBB) that yield tight bounds for interior nodes and precise representation for triangles in the leaf nodes. This innovation allows to streamline the conventional massively parallel BVH traversal, as there is no need to switch between testing for ray intersection in interior nodes and leaf nodes. The results show that the proposed method accelerates ray tracing of incoherent rays between 1.2x–11.8x over the AABB BVH, 1.4x‐4.2x over the 14‐DOP BVH, 1.1x‐2.0x over the OBB BVH, and by 1.1x–1.7x over the SOBB BVH.